Intravitreal aflibercept injection in Indian eyes with retinopathy of prematurity - Vasumathy Vedantham (Indian Journal of Ophthalmology, 2019)
Purpose: To study the efficacy of intravitreal Aflibercept, an anti Vascular Endothelial Growth factor, (anti-VEGF) in Retinopathy of Prematurity (ROP). Methods: This was a retrospective, interventional consecutive case series of 46 Indian eyes which received intravitreal injection of Aflibercept for High risk Prethreshold ROP, Threshold ROP, and Aggressive-Posterior ROP (AP-ROP). Results: Aflibercept was effective in achieving the primary endpoint, namely regression of ROP following the injection in all 46 eyes (100%) at one week following the injection. 32.6% (15/46) of eyes achieved secondary endpoint namely complete vascularization, with no recurrence of ROP at varying time intervals: as early as 15 weeks to as late as 29 weeks after injection, at intervals ranging from 49 to 64 weeks PCA. Conclusion: Intravitreal Aflibercept was effective in inducing complete regression of all types of ROP in all the eyes in our series. In addition, 32.6% of cases did not need a secondary intervention, with no recurrence of ROP and complete vascularization of the retina. In 81.8% of Zone I ROP eyes, Aflibercept facilitated continuation of retinal vascular development following regression of ROP, resulting in less extensive laser during treatment of ROP recurrence. This is the largest series of Aflibercept in ROP, till date as per MEDLINE search.